Phyto-Fabrication Of Palladium Nanoparticles Using Caralluma Fimbriata And Its Potential Antibiofilm Activity Against Dental Pathogens (In Vitro) - Vignesh, M.; Ragavendran, C.; Antony, Delphine Priscilla (Journal of Neonatal Surgery, 2025)
Aim: Phyto-fabrication of palladium nanoparticles using Caralluma fimbriata and its mic and antibiofilm activity against dental pathogens (in vitro). In recent decades, there has been a significant focus on synthesizing metal nanoparticles, such as gold, silver, zinc, platinum, and palladium, within material and biological sciences. Palladium (Pd) has gained particular attention due to its diverse applications as a catalyst in various organic transformations, encompassing carbon-carbon cross-coupling, oxidation, and reduction reactions. Materials and methods: Preparing an aqueous broth from plants for bio-nanoparticle synthesis and biofabrication. Cf-capped pdnp, characterization techniques, antibacterial potential, synthesis of palladium nanoparticle, SEM, XDR analysis Results: The results indicated that Pd NPs possessed antibacterial and antibiofilm activities, which were supported by MIC data, SEM images, and X-ray diffraction patterns. The results suggest that Pd NPs have the potential to serve as effective agents against the tested bacteria and warrant further investigation for their biomedical applications. Conclusion: The comprehensive investigation into the phytofabrication of palladium nanoparticles (Pd NPs) using Caralluma fimbriata and its subsequent evaluation for minimum inhibitory concentrations (MIC) and antibiofilm activity against dental pathogens has provided valuable insights. The in vitro assays conducted in this research enhance the field of green synthesis of nanoparticles and their possible applications in dentistry.